Technical guidelines for strengthening the implementation and tracking of adaptation in climate policies in Africa - Odhiambo, Isaack; Njuguna, Lucy; Mundia, Carolyne; Kimanzi, Meshack; Akoko, Tessie; Binge, Brenda; Kung'u, Fredrick; Denje, Telvin; Awolala, David; Chilambe, Pedro; Wamukoya, George (2025)
This Technical Guideline provides implementation-oriented, Africa-tailored guidance for translating national climate commitments into effective adaptation action. It responds directly to UNFCCC mandates, offering step-by-step support to strengthen adaptation planning, monitoring, evaluation, and learning systems. With a focus on enhancing coherence across NDCs, NAPs, and LT-LEDS, the Guideline prioritizes the agriculture and food systems sectors to bolster resilience. It aims to improve institutional capacity, accountability, and evidence-based decision-making for measurable adaptation progress and tangible outcomes across the continent.